Paralelisme Dan Metafora Dalam Amsal 4:18-19: Analisis Jalan Orang Benar Dan Orang Fasik - Pattinaja, Aska Aprilano (Jurnal Teologi dan Pelayanan Kerusso, 2025)
In The parallelism and metaphors found in the structure of Proverbs 4:18-19 highlight the difference between the choice to be righteous or wicked. Parallelism ensures that the wisdom conveyed can be easily remembered and applied, while metaphor enriches the moral message in a way that stirs emotions and imagination. This parallel structure strengthens the narrative about the choice of life paths, accompanied by the implementation of each individual's decision. Meanwhile, the metaphor depicts the final outcome of each choice. This research aims to serve as a life contemplation for everyone to choose the path of righteousness. Based on a hermeneutic study of the wisdom literature subgenre, this method includes structural analysis of parallelism and poetic devices such as metaphors, as well as exploring its theological meaning within social and cultural contexts, along with its implementation in the ethical and moral lives of individuals. The research identifies three life contemplations: first, the path of the righteous is always illuminated by blessings and promotion; second, the path of the wicked is always in darkness and leads to punishment; and third, the path of the wicked is always a stumbling block. The results of this study affirm that the wisdom in Proverbs remains relevant to modern life. By understanding and applying its principles, one can build a life that is wiser, more moral, and oriented toward God's will, both in personal, spiritual, and social contexts.